Frequency of Upper Gastrointestinal Bleeding As Precipitant of Hepatic Encephalopathy among Patients with Liver Cirrhosis - Muhammad Sajjad Khan, Fahim Ullah Khan, Muhammad Sohail, Muhammad Fahim, Shakeel Akhter, Muhammad Shahid, Adnan Bangash, Sundus Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find frequency of upper gastrointestinal bleeding as precipitant of hepatic encephalopathy among patients with liver cirrhosis. Study design. Descriptive cross sectional study Setting: Gastroenterology and Hepatology Department, Lady Reading Hospital Peshawar. Duration: 6 months 20th December 2018 to 20th June 2019. Material and Methods: In this study a total of 271 patients were observed. History regarding the current illness was taken from the patient or the accompanying caregivers in case patient cannot respond adequately or at all. Emphasize was on the possible precipitant of current HE episode especially symptoms of upper gastrointestinal bleeding like hematemesis and malena. On examination; body temperature, stigmata of chronic liver disease such as hepatic flap, grading of HE and similarly presenting conditions was looked for. Results: In this study mean age was 45 years with SD ± 11.27. Fifty nine percent patients were male whle 41% patients were female. More over 10% patients had upper gastrointestinal bleed with hepatic encephalopathy among patients with liver cirrhosis. Conclusion: Our study concludes that the frequency of upper gastrointestinal bleed was 10% as precipitant of hepatic encephalopathy among patients with liver cirrhosis. Keywords: Upper Gastrointestinal Bleed, Hepatic Encephalopathy, Liver Cirrhosis.